Bimanual Microincision Cataract Surgery versus Coaxial Microincision Cataract Surgery: A Meta-Analysis of Randomized Controlled Trials and Cohort Studies - Chenxi Fu; Naipin Chu; Xiaoning Yu; Ke Yao (Journal of Ophthalmology)
Purpose. This meta-analysis was conducted to compare the intraoperative and postoperative outcomes of bimanual microincision cataract surgery (B-MICS) and coaxial microincision cataract surgery (C-MICS). Methods. Three databases were searched for papers that compared B-MICS and C-MICS from inception to June 2016. The following intraoperative and postoperative outcomes were included in the final meta-analysis: ultrasound time (UST), effective phacoemulsification time (EPT), balanced salt solution use (BSS use), mean surgery time, best-corrected visual acuity (BCVA), central corneal thickness (CCT), and increased CCT. Results. There were no statistically significant differences in mean surgery time, UST, BSS use, BCVA, CCT, or increased CCT (one subgroup at postoperative day 7-8 and another subgroup at postoperative day 30). However, there was less EPT needed during surgery (p<0.01) and lower levels of increased CCT at postoperative day 1 (p=0.02) in the B-MICS group compared with the C-MICS group. Conclusions. The EPT was shorter and increased CCT was less at postoperative day 1 in the B-MICS group. There were no statistically significant differences in other intraoperative and postoperative outcomes between the B-MICS group and the C-MICS group. B-MICS is an efficient and safe cataract surgery procedure.